Enhanced Detection of Mycobacterium bovis-Specific T Cells in Experimentally-Infected Cattle - Boggiatto, Paola M.; Kanipe, Carly R.; Palmer, Mitchell V. (Frontiers in Veterinary Science, 2021)
Bovine tuberculosis (bTB), caused by infection with Mycobacterium bovis, continues to be a major economic burden associated with production losses and a public health concern due to its zoonotic nature. As with other intracellular pathogens, cell-mediated immunity plays an important role in the control of infection. Characterization of such responses is important for understanding the immune status of the host, and to identify mechanisms of protective immunity or immunopathology. This type of information can be important in the development of vaccination strategies, diagnostic assays, and in predicting protection or disease progression. However, the frequency of circulating M. bovis-specific T cells are often low, making the analysis of such responses difficult. As previously demonstrated in a different cattle infection model, antigenic expansion allows us to increase the frequency of antigen-specific T cells. Moreover, the concurrent assessment of cytokine production and proliferation provides a deeper understanding of the functional nature of these cells. The work presented here, analyzes the T cell response following experimental M. bovis infection in cattle via in vitro antigenic expansion and re-stimulation to characterize antigen-specific CD4, CD8 and gd T cells and their functional phenotype, shedding light on the variable functional ability of these cells. Data gathered from these studies can help us better understand the cellular response to M. bovis infection and develop improved vaccines and diagnostic tools.